2007
DOI: 10.1523/jneurosci.3759-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry of Anticipatory Activity in Visual Cortex Predicts the Locus of Attention and Perception

Abstract: Humans can use advance information to direct spatial attention before stimulus presentation and respond more accurately to stimuli at the attended location compared with unattended locations. Likewise, spatially directed attention is associated with anticipatory activity in the portion of visual cortex representing the attended location. It is unknown, however, whether and how anticipatory signals predict the locus of spatial attention and perception. Here, we show that prestimulus, preparatory activity is hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
112
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(130 citation statements)
references
References 74 publications
(107 reference statements)
16
112
2
Order By: Relevance
“…The orientation discrimination task required subjects to direct spatial attention to the left lower quadrant. Important processes for acquisition of the task include filtering of distracters at multiple unattended locations (36), as well as coding of the locus of attention by gradients of activity across spatial maps (37,38). Hence, a high degree of coherence between stimulus-specific regions in visual cortex, before any experience, may facilitate the subsequent parsing of relevant from irrelevant information, and facilitate the reweighting of functional connections among different quadrants in visual cortex.…”
Section: Discussionmentioning
confidence: 99%
“…The orientation discrimination task required subjects to direct spatial attention to the left lower quadrant. Important processes for acquisition of the task include filtering of distracters at multiple unattended locations (36), as well as coding of the locus of attention by gradients of activity across spatial maps (37,38). Hence, a high degree of coherence between stimulus-specific regions in visual cortex, before any experience, may facilitate the subsequent parsing of relevant from irrelevant information, and facilitate the reweighting of functional connections among different quadrants in visual cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we show that modulation in the visual cortex is topographically and shape specific and mainly consists of the filtering of sensory-evoked responses to novel (untrained) shapes in the attended quadrant, which presumably leads to a more specific response to the trained shape. The presence of training-related modulation in the visual cortex homologous to the representation of the trained quadrant is not surprising in light of several recent fMRI studies (27,28). These studies suggest that modulations in the visual cortex are not restricted to attended locations, as previously believed, but extend to unattended locations, especially those in the opposite hemisphere homologous to the attended ones.…”
Section: Resultsmentioning
confidence: 62%
“…These studies suggest that modulations in the visual cortex are not restricted to attended locations, as previously believed, but extend to unattended locations, especially those in the opposite hemisphere homologous to the attended ones. This pattern reflects a specific computational mechanism for coding the locus of attention in a cortical map based on activity difference between attended and unattended locations (27,29).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Such a modulation can theoretically take multiple forms. It has been suggested that it involves the variation of baseline activity in the absence of visual stimulation, the enhancement of visual responses to targets at attended locations, and possibly the suppression of unwanted information at the unattended location (e.g., Kastner and Ungerleider 2000;Luck et al 1997;Sylvester et al 2007Sylvester et al , 2009). However, the hypothesis that orienting visuospatial attention improves single-target detection by facilitating visual processing appears questionable (Fecteau and Munoz 2005;Kahn et al 2010).…”
mentioning
confidence: 99%